(untitled) (Research, Society and Development, 2022)
From the beginning of studies to the present day, semiotics has been used in several subfields of activity. Given this interdisciplinary, understanding more about communication and semiotics research will help to elucidate the knowledge of the field, bringing subsidies for future studies and communication approaches not explored in Brazilian research. Thus, the objective of this work was to carry out a literature review on an indexed international basis, through the Theory of Consolidated Meta-Analytical Approach - TEMAC, which uses bibliometric principles to outline the panorama of the theme. As a result, it was possible to conclude that Brazil appears in a prominent place, occupying the seventh world position of the countries that publish the most. However, it is important to highlight that quantity is not always a meaning of scientific relevance, since no Brazilian author was cited in the “co-citation” and “bibliographic coupling” searches. Revealing that although Brazil produces in quantity, the articles are not being cited; suggesting little relevance of the themes investigated. The most cited authors, the ones who publish the most, funding institutions and universities that do most research on semiotics and communication were also raised in the study.